Multifaceted roles of STING in tumors: from molecular mechanisms to therapeutic strategies - Hussain, Aashiq; Wen, Linchun; Wang, Rui (Frontiers in Chemical Biology, 2025)
Since the discovery of Stimulator of Interferon Genes (STING) as a key element in recognizing cytosolic DNA and initiating interferon (IFN) production, substantial research has been conducted to comprehend the precise molecular process of its activation for the treatment of tumor and immune-related diseases. However, new research has enhanced our understanding of STING biology and shown additional major functions of STING that go beyond its capacity to stimulate (Interferon-Stimulated Genes)(ISGs). This mini-review article highlights important details of the established STING biology, including TBK1-IRF3 activation, the NF-κB and MAPK pathway, endoplasmic reticulum (ER) stress and autophagy, and lysosome-induced degradation. We also provide an overview of the independent functions of cGAS and STING, unresolved questions that need to be addressed, and directions for future research.